Assessment of water pollution arising from copper mining in Zambia: a case study of Munkulungwe stream in Ndola, Copperbelt province - Mudenda, Lee (Centre for Bioprocess Engineering Research, 2018)
Water pollution is recognized as one of the major environmental problems in the mining industry. This has been compounded with an increase in agriculture activities. Water pollution is a major problem on copper and coal mines throughout the world and Zambia, the focus of this study, is no exception. Worldwide freshwater resources, which provide important ecosystem services to humans, are under threat from rapid population growth, urbanization, industrialization and abandonment of wastelands. There is an urgent need to monitor and assess these resources. In this context, the physical, chemical and ecological water quality of the Munkulungwe Stream located on the Copperbelt of Zambia, was assessed with possible contamination from Bwana Mkubwa TSF, agriculture activities and subsequent impact on the surrounding community. The chemical and physical parameters were assessed at four sampling locations. Sampling site S1 was located on the Munkulungwe stream upstream of Bwana Mkubwa TSF, S2, S3 and S4 were on the main stream downstream of Bwana Mkubwa TSF. In addition, a macroinvertebrate composition analysis was performed to estimate the quality of water using the biotic index score. Finally, the relationship between physiochemical parameters and biotic index score was analysed to interrogate their inter-relationship with respect to water quality. The results showed that the average values of dissolved oxygen (DO) of 4.52 mg/l, turbidity (40.96 NTU), Co (0.24 mg/l), Pb (0.25 mg/l), Fe (0.36 mg/l) and Mn (0.22 mg/l) downstream exceeded international standards for drinking water. Upstream, the values of Co, Pb, Fe and Mn were within acceptable standards for drinking water, DO and turbidity were above acceptable standards. The metal concentration and total dissolved solutes were impacted by closeness to the mine tailings deposit with the heavy metal concentration being highest at S2 and S3. Moreover, high turbidity levels revealed that land erosion induced by agriculture activities is a severe problem in the area. Physical parameters were high in the rainy season due erosion escalated by rains while chemical parameters were high post rainy season. During the rainy season, the chemical contaminants are diluted and thus they are not such a big impact, but they tend to concentrate up during the dry MDNLEE001 III season. The stream at sampling points S2 and S3 was dominated by species tolerant (leech, Isopod and Snail: Pouch) and semi tolerant (Blackfly larvae and Amphipod or Scud) to pollution. The change in season influenced the composition of macroinvertebrates, with the number of species increased post rainy season. The average biotic index score (2.5) showed that the stream condition is not good, it is slightly polluted. The results showed that water quality downstream was substantially affected by Bwana Mkubwa TSF, agriculture activities and is likely to affect human health and food security. It is recommended that groundwater surrounding tailings dams should be monitored in both active and abandoned mines. Curtain boreholes around a tailings dam can be drilled and the water extracted and treated so that it doesn't contaminate other water bodies. To improve the environmental management of mining related impacts in Zambia, mining areas should be completely rehabilitated. There is need for remediation strategies for abandoned mine sites. Constructed wetlands, roughing filtration and phytoremediation are highly promising techniques, as they are reliable, cheap, effective and sustainable.